Colony-forming unit assay as a potency test for hematopoietic stem/progenitor cell products - Škifić, Marijana (Array, 2019)
Colony-forming unit (CFU) assay is a short-term culture assay used for the detection of functionally active hematopoietic progenitor cells (HPCs) in the in vitro setting. This potency assay enables the identification of colony-producing HPCs in any type of hematopoietic stem cell/progenitor product (HSC/P) including bone marrow (BM), cord blood (CB) and mobilized peripheral blood (MPB). It has been shown that the frequency of HPCs in BM, MPB and CB cellular products directly correlates with the engraftment of both neutrophils and platelets as well as with the overall survival of recipients following hematopoietic stem cell transplantation which makes the CFU assay a good quality parameter for the prediction of engraftment success. The aim of this article is to provide an overview of different approaches to setting up the CFU assay with an emphasis on different sample preparation techniques, cell plating density and colony identification and enumeration used by different laboratories.